Unihorn Pyometra in a Bitch - S. Satheshkumar; M. Murugan; A. Ganesan; S. Dharmaceelan; Vishnugurubaran; M. Bavadharani (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Canine pyometra is the most common diestrual uterine disease of intact bitches and is characterized by accumulation of purulent material in the uterine lumen, typically occurring during or immediately following a period of progesterone dominance. Pyometra can be classified as open-cervix or closed-cervix, with the latter being a medical emergency requiring rapid intervention to prevent subsequent sepsis and potential patient death (Pretzer, 2008).